Ruling out nosocomial transmission of Cryptosporidium in a renal transplantation unit: case report. Issue 1 (December 2016) - Brunet, J.; Lemoine, J.; Pesson, B.; Valot, S.; Sautour, M.; Dalle, F.; Muller, C.; Borni-Duval, C.; Caillard, S.; Moulin, B.; Pfaff, A.; Razakandrainibe, R.; et al.
Abstract Background Cryptosporidium spp. is a ubiquitous parasite affecting humans as well as domestic and wild vertebrates, causing diarrhea in both immunocompetent and immunocompromised hosts worldwide. Its transmission occurs primarily by the fecal-oral route. In humans, C. parvum andC. hominis are the most prevalent species, whereas immunocompetent and immunocompromised individuals can also be infected by other zoonotic species. Renal transplant patients are prone to develop cryptosporidiosis, which can induce severe and life-threatening diarrhea. Case presentation We report here a series of nearly concomitant cases of acute symptomatic cryptosporidiosis in three renal transplant patients attending the Strasbourg University Hospital Nephrology Unit. The clinical presentation was persistent diarrhea and acute renal failure. The diagnosis was confirmed by microscopic stool examination using a modified Ziehl-Neelsen staining method and species identification by molecular tools. All patients were treated with nitazoxanide and recovered from diarrhea after 14 days of therapy. Conclusion Genotypic species identification was not consistent with an epidemic context, thus underlining the need for genotyping to monitor at risk patients.